Nur Hidayahan: Komodifikasi Dakwah - Risdayah, Enok (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2020)
ABSTRACT Da'wah can be done through various approaches, one of the approaches is through culture. As was done by Raden Hidayat Suryalaga, through Nur Hidayah. This study aims to determine how the process of preaching through a cultural approach, namely the art of Nur Hidayah, understanding Nur Hidayah in its entirety, both from the historical and content side, Nur Hidayah, and the commodification of Da'wah and Nur Hidayah. The method used is qualitative with a descriptive approach. The author conducted a direct interview with Hidayat in 1996, and observations within the Atikan Sunda Foundation. The results showed that there was innovation both in the formulation of da'wah and in the content of Nur Hidayah. This innovation is a form of commodification because in the end, besides generating use-value it also generates exchange value. The impact of this research is expected to enrich the treasures of piety both in terms of methods and in terms of content. Keywords: Nur Hidayah; Dakwah; commodification. ABSTRAK Dakwah dapat dilakukan melalui berbagai pendekatan, salah satu pendekatan adalah melalui kebudayaan. Seperti yang dilakukan oleh Raden Hidayat Suryalaga, melalui Nur Hidayah. Penelitian ini bertujuan untuk mengetahui bagaimana proses dakwah melalui pendekatan kebudayaan yaitu seni Nur Hidayah,Â memahami Nur Hidayah secara utuh, baik dari sisi historis maupun dari sisi konten, Nur Hidayah, dan bentuk komodifikasi Dakwah dan Nur Hidayah. Adapun metode yang digunakan adalah kualitatif dengan pendekatan deskriptif. Penulis mengadakan wawancara langsung dengan Hidayat pada tahun 1996, dan observasi di lingkungan Yayasan Atikan Sunda. Adapun hasil penelitian menunjukkan bahwa terjadi inovasi baik pada formulasi dakwah maupun pada konten Nur Hidayah. Inovasi tersebut merupakan bentuk komodifikasi karena pada akhirnya, selain menghasilkan nilai guna juga menghasilkan nilai tukar. Dampak dari penelitian ini diharapkan dapat memperkaya khazanah kedakwahan baik dari sisi metode maupun dari segi konten. Kata Kunci: Nur Hidayah; Dakwah; komodifikasi.